Increasing Activities and Science Learning Outcomes on Environmental Pollution Materials Through Contextual Teaching and Learning (CTL) Approaches for Class VII-A Students of MTsN 2 Aceh Barat Academic Year 2021/2022 - Ismarlin, Ismarlin (LUMBUNG AKSARA, 2022)
This research is motivated by the low value of science learning outcomes on Environmental Pollution material caused by several factors, namely the way teachers carry out learning is still conventional so students tend to be passive. Based on these problems, the research objective to be achieved is to increase the activities and learning outcomes of Science on Environmental Pollution by applying the Contextual Teaching and Learning (CTL) approach to Class VII-A students of MTsN 2 Aceh Barat for the 2021/2022 academic year. The method used in this research is (CAR) which adapts the Kemmis & Mc. Taggart with two cycles, which in each cycle two actions are performed. The subjects of this study were students of VII-A MTsN 2 Aceh Barat, totaling 36 students. The results of science learning on Environmental Pollution by applying the CTL approach are proven to be able to increase student activities and learning outcomes. This is evidenced by an increase in student activity from before the improvement only 7 students or 19.44%, increased to 26 students or 72.22% in the first cycle, and 91.67% or 33 students in the second cycle, and an increase in student learning outcomes. from the average before the improvement was only 58.33, rose to 67.50 in the first cycle, and 76.94 in the second cycle, with a learning completeness level of 6 students (16.67%) in the initial conditions, 61.11% or 22 students in the first cycle, 34 students or 94.44% in the second cycle, and there are still two students (5.56%) who have not completed. The conclusion is that the application of the CTL approach is proven to be able to increase activities and learning outcomes in Science on Environmental Pollution for Class VII-A students of MTsN 2 West Aceh in the 2021/2022 academic year.